Photomediated ion dynamics enables multi-modal learning, memory and sensing in ultralow-voltage organic electrochemical device - Guocai Liu; Wei Wen; Cong Shan; Haojie Huang; Yao Zhao; Yangshuang Bian; Yunlong Guo; Hui Huang; Yunqi Liu (Nature Communications)
Abstract Ion signaling enables biological systems to implement learning, memory and sensing tasks in an energy-efficient manner. Organic electrochemical transistors are promising building blocks for mimicking ion-driven processes in the organism due to the iontronic coupling. However, the ion kinetics of diffusion back to the electrolyte poses a challenge in achieving non-volatility at ultralow gate voltages (V G) required to mimic human learning and memory capabilities. Here we report a non-volatile heterojunction organic electrochemical device (nHOED) driven by photomediated ion trap and release dynamics. Due to the efficient separation of photogenerated charges within the heterojunction, the holes can be tightly trapped by anions at the photoactive layer–channel interface. This enables the device to realize multibit memory (over 100 distinct memory states) over a broad wavelength spectrum of 365–660 nm. Consequently, the nHOED can effectively replicate the learning, memory and sensing capabilities of the human neural system. In addition, the protocol avoids the injection of trap-function anions into the channel, facilitating the device to achieve non-volatility in the absence of V G. Moreover, by employing a vertical traverse architecture that offers the advantage of a short channel, the operating voltage of the nHOED has been reduced to 0.1 V.